MAMA SIMONA: ANCESTRAL AND CONTEMPORARY MEMORY - Bolívar Yapura, Wilber (2015)
This work focuses on understanding one of the most important mountains surrounding the valley of Cusco , in pre-Hispanic times it was a tutelary Apu very important, and that its name was changed according to the situations of social actors of those times , whose validity still remains . It is given different names like Apian , aspire and Yauira , again aspire , again Apian and Yauirac from 1571-1653 recorded by chroniclers of those times. Then with the removal of idolaters is assigned the name of Simon who was quechuizado to Quimon and finally the Mama Simona and converted into a female mountain spirit. Whose importance is explained by the role it plays in the ancestral memory and its claim as such in our times.